Synthesis and Antimicrobial Activity of Some Pyrazoline Derivatives - Ahirwar, M.K.; Gautam, N.; Shrivastava, S.P. (Asian Journal of Chemistry, 2010)
The objective of present study is to synthesize and screening of antimicrobial activity of some derivatives of pyrazoline. 1H-[4-nitro phenyl-5-(substituted phenyl)]pyrazoline has been used as a precursor to synthesize some biologically active heterocycles. Reaction of 1-(4-nitrophenyl)- 3-(substituted phenyl) prop-2-en-1-one with hydrazine hydrate gave 1H-(3-nitrophenyl-5-(substituted phenyl) pyrazoline which on reaction with benzoyl chloride in pyridine gave 1-benzoyl-(4-nitrophenyl)-5-(substituted phenyl) prazoline and on reaction with acetic acid yields 1-acetyl-(4-nitrophenyl)-5-(substituted phenyl) pyrazoline derivatives. Several derivatives have been synthesized and screened for their antimicrobial efficacy against Bacillus subtilis, Escherichia coli, Staphylococcus aureus and Klebsiella pneumoniae. Antifungal activity against, Aspergillus flavus, Fusarium oxisporum, Aspergillus niger and Trichoderma viridae.